Chapter La polemica confessionale fra ortodossi e cattolici negli scritti di Gerasim Zelić - Fin, Monica (Biblioteca di Studi Slavistici, 2019)
The paper summarizes the results of a research project dedicated to Serbian archimandrite Gerasim Zelić (1758-1828), one of the main protagonists of the interconfessional polemic that engulfed the Serbian Orthodox community living in Dalmatia between the 17th and 19th centuries. Firstly, the paper describes the activities that were carried out during the project, particularly the digitalization and on-line publication of a corpus of manuscript documents connected to Zelić. Secondly, it presents the results of a historical and culturological analysis conducted on the aforementioned documents.